Variability in oxidative stress-related genes (SOD2, CAT, GPX1, GSTP1, NOS3, NFE2L2, and UCP2) and susceptibility to migraine clinical phenotypes and features - Papasavva, Maria; Vikelis, Michail; Siokas, Vasileios; Katsarou, Martha-Spyridoula; Dermitzakis, Emmanouil V.; Raptis, Athanasios; Kalliantasi, Aikaterini; Dardiotis, Efthimios; Drakoulis, Nikolaos (Frontiers in Neurology, 2023)
Introduction Migraine is a complex disorder with genetic and environmental inputs. Cumulative evidence implicates oxidative stress (OS) in migraine pathophysiology while genetic variability may influence an individuals' oxidative/antioxidant capacity. Aim of the current study was to investigate the impact of eight common OS-related genetic variants [rs4880 (SOD2), rs1001179 (CAT), rs1050450 (GPX1), rs1695 (GSTP1), rs1138272 (GSTP1), rs1799983 (NOS3), rs6721961 (NFE2L2), rs660339 (UCP2)] in migraine susceptibility and clinical features in a South-eastern European Caucasian population. Methods Genomic DNA samples from 221 unrelated migraineurs and 265 headache-free controls were genotyped for the selected genetic variants using real-time PCR (melting curve analysis). Results Although allelic and genotypic frequency distribution analysis did not support an association between migraine susceptibility and the examined variants in the overall population, subgroup analysis indicated significant correlation between NOS3 rs1799983 and migraine susceptibility in males. Furthermore, significant associations of CAT rs1001179 and GPX1 rs1050450 with disease age-at-onset and migraine attack duration, respectively, were revealed. Lastly, variability in the CAT, GSTP1 and UCP2 genes were associated with sleep/weather changes, alcohol consumption and physical exercise, respectively, as migraine triggers. Discussion Hence, the current findings possibly indicate an association of OS-related genetic variants with migraine susceptibility and clinical features, further supporting the involvement of OS and genetic susceptibility in migraine.